ANALISA SWOT PADA BISNIS RUMAHAN, STUDI KASUS PADA BISNIS LAUNDRY KILOAN - Abdullah Umar; Agung Hari Sasongko; Glory Aguzman; Sugiharto Sugiharto (BBM (Buletin Bisnis & Manajemen), 2016)
Business can be done anywhere and by anyone. Where the purpose of a business for some people is different. Among others there are which aims to increase revenue. So with that reason, began to grow home-based business scale. Where businesses are done by the community and are planted in housing. One home-based business is the laundry. Laundry business kilogram is now very widespread, almost in every street can be found Landry. However, if carelessly in managing this business, then the business can be folded more quickly. So it takes some analysis, including marketing mix, where to open this business, you need to know the 4Ps. Product, Price, Place and Promotion. In addition to the marketing mix, it is necessary to do a SWOT. This research was conducted using quantitative and qualitative methods. Where data collection is done by observation and interviews with business owners, employees and customers. The results of this study will be able to look at the factors that influence the laundry as a home-based business with a view of the internal and external factors. Keywords: Home Industru, Marketing Mix, SWOT Analysis